The Meanings of Face as Manifested in Moroccan Arabic Idioms and Proverbs - Khatib, Mohammed (International Journal of Language and Literary Studies, 2024)
Face plays a pivotal role in human interaction. Indeed, it is a multifaceted construct that has various connotative meanings in different cultures. It has been used, in various contexts, to refer to social value, social status, self- image, reputation, dignity, honour, and several other notions. In this regard, the aim of this study is to explore the meanings and concepts associated with face in Moroccan Arabic (MA) idiomatic expressions and proverbs. To achieve this objective, the study used a corpus of 30 items from MA. Many expressions were collected by the researcher using his knowledge of MA as a native speaker and his discussions with different people both face-to-face and on social media. Some items of the corpus were collected from available collections of proverbs. The selection of the data has been based on the principle of currency. The data were transliterated and translated into English to explore the meanings and concepts associated with face in MA. The study showed that face in the Moroccan culture is closely related to shame or Moroccan hshuma and that it is associated with the inner state and character of people more than it does in English.